2017
DOI: 10.4067/s0717-95022017000300055
|View full text |Cite
|
Sign up to set email alerts
|

Stature and its Estimation Utilizing Arm Span Measurements in Kosovan Adults: National Survey

Abstract: SUMMARY:The purpose of this research is to examine stature in both Kosovan sexes as well as its association with arm span, as an alternative to estimating stature. A total of 1623 individuals (830 boys and 793 girls) participated in this research. The anthropometric measurements were taken according to the protocol of ISAK. The relationships between stature and arm span were determined using simple correlation coefficients at a ninety-five percent confidence interval. Then a linear regression analysis was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
12

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 21 publications
(29 reference statements)
2
35
1
12
Order By: Relevance
“…There are lots of scientific findings which confirms that the measurement of standing height is a vitally important variable when assessing nutritional status (cited in Arifi et al, 2017a;Datta Banik, 2011;, as well as when assessing the growth of children, evaluating the basic energy requirements, adjusting the measures of physical capacity and predicting the drug dosage and setting standards of physiological variables such as muscle strength, metabolic rate, lung volumes and glomerular filtration (Golshan, Amra, & Hoghogi, 2003;M. Golshan, Crapo, Amra, Jensen, & R. Golshan, 2007;Mohanty, Babu, & Nair, 2001;Ter Goon, Toriola, Musa, & Akusu, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There are lots of scientific findings which confirms that the measurement of standing height is a vitally important variable when assessing nutritional status (cited in Arifi et al, 2017a;Datta Banik, 2011;, as well as when assessing the growth of children, evaluating the basic energy requirements, adjusting the measures of physical capacity and predicting the drug dosage and setting standards of physiological variables such as muscle strength, metabolic rate, lung volumes and glomerular filtration (Golshan, Amra, & Hoghogi, 2003;M. Golshan, Crapo, Amra, Jensen, & R. Golshan, 2007;Mohanty, Babu, & Nair, 2001;Ter Goon, Toriola, Musa, & Akusu, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A great number of studies have shown that body height measurement is a valuable factor which is highly aff ective on the state of nutrition in adults (cited in Arifi et al, 2017a;, as well as for estimating the growth rate in children, evaluating the basic energy needs, adjusting the physical capacity measures, as well as for estimating the amount of taking certain medications and a number of other things, such as muscle strength assessment, metabolic processes, lung capacity, and the like. (Golshan, Amra, & Hoghogi, 2003;M.…”
Section: Introductionmentioning
confidence: 99%
“…All above-mentioned have confi rmed the necessity for developing separate standing height models for each population on account of ethnic diff erences and the recent study conducted by Popovic and his collaborators (Popovic et al, 2017a; who have analyzed the entire Kosovan population and have found specifi c correlation coeffi cient in Kosovan male (r=0.669) and female (r=0.625) population; however, some recent studies have also confi rmed the regional diff erences between the same ethnic groups too (Arifi , 2013;Arifi et al, 2017b;Milasinovic et al, 2016a;Milasinovic et al, 2016b;Popovic et al, 2017b), which caused the need for additional caution, mostly due to the reason one of them was sampled by Western-Kosovans. Th erefore, the main goal of this research was to test the hypothesis if above-mentioned facts are true for the Eastern-Kosovans, that is, for the one of fi ve Kosovan regions.…”
Section: Discussionmentioning
confidence: 99%
“…Th e mentioned variations might be the case with foot length predictions too, mostly due to the fact that the Dinaric Alps population has specifi c body composition than national as well as regional point of view (Popovic, 2017). Even though many studies with this essence are available on neighboring countries as well as worldwide population, only narrow data is available on Kosovan subjects, just one conducted by Popovic, Arifi and Bjelica (2017a;) that has covered whole Kosovan population, and one regional analyses that confi rmed Western-Kosovans have specifi c standing height/foot length ratio, comparing to general population in Kosovo (Popovic, Gardasevic, Masanovic, Arifi , & Bjelica, 2017b;Masanovic, Gardasevic, & Arifi , 2018). Considering rather sparse recent scientifi c literature, the purpose of this research was to examine the standing height in both Eastern-Kosovan genders and its association with foot length.…”
Section: Relationship Foot Length/body Height In Eastern-kosovan Adolmentioning
confidence: 99%
See 1 more Smart Citation